Optimalisasi Potensi Lokal Desa Linggasari, Banyumas melalui Inovasi Olahan Mie Sari Bengkuang - Tin Herawati; Aulia Uswatun Nur Khasanah; Siti Rahayu; Devi Fitriani; Ilham Driartama; Mukti Teguh Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Linggasari Village is one of the villages located in Kembaran sub-district, Banyumas district, Central Java. Agriculture in Linggasari Village is quite advanced, especially in the Bengkuang commodity which is an icon of the Linggasari village. The potential of Jicama agricultural products is higher than other agricultural products such as rice, corn and soybeans. In Linggasari, bengkuang has been processed into various local products such as crackers, mochi, and masks. These products have been sold by the public but are limited due to a lack of interest. In addition, many people still sell whole jicama at a low price. Even though it has been sold at a low price, buyers' interest in jicama is still low so that many jicama are rotten because they are not sold and are just neglected. The purpose of this community service is to educate the community through training in making jicama processed innovations, namelysari bengkuang noodles to increase economic value and optimize the existing potential in Linggasari Village. The community service method used is through training in making noodles sari bengkuang directly to partners of the Kelompok Wanita Tani (KWT) and Pemberdayaan Kesejahteraan Keluarga (PKK). The results achieved from this service activity were the creation of an innovation, namely Sari Bengkuang Noodles. Keywords: innovation product, jicama, sari bengkuang noodles